Organic matter accumulation in the Upper Cretaceous Qingshankou and Nenjiang Formations, Songliao Basin (NE China): Implications from high-resolution geochemical analysis. (April 2019) - Xu, Jinjun; Liu, Zhaojun; Bechtel, Achim; Sachsenhofer, Reinhard F.; Jia, Jianliang; Meng, Qingtao; Sun, Pingchang
Abstract: The Songliao Basin is well-known as one of most prolific petroleum basins in China. Information regarding Upper Cretaceous organic matter (OM) accumulation within black shales of the Qingshankou and Nenjiang Formations (Fm) can be obtained by geochemical analyses. Two oil shale successions at the bottom of the Qingshankou Fm first member (K2 qn1 ) and Nenjiang Fm second member (K2 n2 ) are investigated in high resolution to reveal the factors that govern OM accumulation. Within the two target profiles, combined petrological and geochemical results indicate that OM accumulation can be divided into two phases: (i) a lower phase characterized by high primary productivity, enhanced input of terrigenous OM and anaerobic conditions of OM deposition (TOC maximum 18.25 wt%) and (ii) an upper phase of lower primary productivity and anoxic to dysoxic conditions in bottom water (TOC maximum 9.45 wt%). Alternations of warmer and wetter climatic conditions provided the nutrients, and fluctuations in lake level are suggested to be responsible for differences in redox conditions and bioproductivity between the two phases. Marine ingressions enhanced OM preservation by promoting bottom water salinity (e.g., anaerobic conditions with brackish-saline water within K2 qn1 lower phase). The identification of different OM accumulation mechanisms by high-resolution geochemical analyses are expected to improve the prediction of high quality source rocks within uniform depositional environments. Highlights: Different formation mechanisms of OM-rich successions are outlined. Undulated paleoclimate controlled OM accumulation. Hydrocarbon potential was governed by OM sources and preservation. OM accumulation models are summarized.